Esotericism, Myth and Subversion in Alan Moore’s "Promethea" - Sánchez Pérez, Carlos (Amaltea. Revista de Mitocrítica, 2021)
The aim of this article is to explore the intersection between esotericism and myth in Alan Moore’s Promethea. I will start with an approach to what we consider “esotericism”, followed by an exposition of the characteristics of Hermetism and its legacy, which are vital to understand Moore’s work. Finally, I will analyze the ending of the work in order to understand how the interaction between myth and esotericism take place.